Current status and unanswered questions on the use of Denosumab in giant cell tumor of bone. Issue 1 (December 2016) - Gaston, Czar; Grimer, Robert; Parry, Michael; Stacchiotti, Silvia; Dei Tos, Angelo; Gelderblom, Hans; Ferrari, Stefano; Baldi, Giacomo; Jones, Robin; Chawla, Sant; Casali, Paolo; LeCesne, Axel; et al.
Abstract Denosumab is a monoclonal antibody to RANK ligand approved for use in giant cell tumour (GCT) of bone. Due to its efficacy, Denosumab is recommended as the first option in inoperable or metastatic GCT. Denosumab has also been used pre-operatively to downstage tumours with large soft tissue extension to allow for less morbid surgery. The role of Denosumab for conventional limb GCT of bone is yet to be defined. Further studies are required to determine whether local recurrence rates will be decreased with the adjuvant use of Denosumab along with surgery. The long term use and toxicity of this agent is unknown as is the proportion of patients with primary or secondary resistance. It is advised that complicated cases of GCT requiring Denosumab treatment should be referred and followed up at expert centres. Collaborative studies involving further clinical trials and rigorous data collection are strongly recommended to identify the optimum use of this drug.